2006
DOI: 10.1007/s11267-006-9031-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pollution of the Plitvice Lakes by Water and Sediment Analyses

Abstract: The process of eutrophication in form of intense plant growth has been observed in some lakes and water streams at the Plitvice Lakes National Park in central Croatia. Here we investigate whether this phenomenon is a consequence of anthropogenic pollution or due to naturally produced organic matter in the lakes. We applied chemical analysis of water at two springs and four lakes (nutrients, dissolved organic carbon (DOC), trace elements) and measurements of surface lake sediments (mineral and organic fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Human influence on tufa deposition has been so profound during late historical times that deforestation, improved drainage and pollution are perceived as the most common causes for their depositional decline (Goudie et al, 1993;Taylor et al, 1998;Nyssen et al, 2004). Recent case studies have documented a range of anthropogenic-associated environments including Plitvice lakes -Croatia (Horvatin ci c et al, 2006), coastal tufa of the Leeuwin-Naturaliste geographic region -Western Australia (Forbes et al, 2010), Huanglong ravine and Xiangshui River -China (Liu et al, 2011;Zhang et al, 2012). In all cases, carbonate deposition rates have declined significantly as a result of phosphate pollution caused by tourism and agricultural activities within the catchment areas.…”
Section: Anthropogenic Influence On Natural Environmentsmentioning
confidence: 99%
“…Human influence on tufa deposition has been so profound during late historical times that deforestation, improved drainage and pollution are perceived as the most common causes for their depositional decline (Goudie et al, 1993;Taylor et al, 1998;Nyssen et al, 2004). Recent case studies have documented a range of anthropogenic-associated environments including Plitvice lakes -Croatia (Horvatin ci c et al, 2006), coastal tufa of the Leeuwin-Naturaliste geographic region -Western Australia (Forbes et al, 2010), Huanglong ravine and Xiangshui River -China (Liu et al, 2011;Zhang et al, 2012). In all cases, carbonate deposition rates have declined significantly as a result of phosphate pollution caused by tourism and agricultural activities within the catchment areas.…”
Section: Anthropogenic Influence On Natural Environmentsmentioning
confidence: 99%
“…Abundance and diversity of caddisflies at tufa barriers in the Plitvice Lakes NP is controlled by the availability of food resources, variety of microhabitats (with respect to current velocity and substrate type) for larval stages (MINSHALL, 1984;HABDIJA et al, 2004;BROOKS et al, 2005;MILIŠA et al, 2006a), which is revealed by the longitudinal distribution preferences of caddisflies (GRAF et al, 2002(GRAF et al, , 2008. Thus the highest number of individuals and species were collected at the Labudovac barrier, located downstream Prošče Lake where the concentration of organic matter is among the highest within this barrage-lakes system (HORVATINČIĆ et al, 2006), providing a wide range of food resources for insect larvae (see also WARINGER, 1996;WIBERG-LARSEN et al, 2000;HABDIJA et al, 2004;MILIŠA et al, 2006a).…”
Section: Differences In Community Composition Between Tufa Barriers -mentioning
confidence: 99%
“…in last ∼50 years ( Figure 2). It also correlated with slight increase of organic carbon concentration in top 5 cm of sediment, 3.7 -4.5% and 3% for lakes Prošće and Kozjak, respectively, and below 10 cm it was 2.9 -3.2% for Lake Prošće and 1.6 -2.2% for Lake Kozjak [9].…”
Section: Resultsmentioning
confidence: 72%
“…Qualitative mineralogical analyses have shown that dominant component of inorganic fraction of the sediment is calcite (70 − 85%) with a few percent of dolomite and quartz, and the minor components, detected in some samples, are aragonite, quartz, feldspars and minerals of the filosilicates group [9]. Calcite is mainly authigenic, i.e., it precipitates from the DIC in water.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation